Composición de especies leñosas en comunidades invadidas en montañas del centro de Argentina: su relación con factores ambientales locales - Zeballos, Sebastián Rodolfo (2014)
Invasions by exotic woody species are threatening ecosystem functions worldwide. The spread and subsequent replacement of native forest by exotic dominated stands is particularly evident nearby urban centers were exotic propagule pressure is highest. Yet, there is a lack of information on the environmental factors that underlie these replacements. In this study we addressed the following questions: (1) is there a local spatial segregation between the dominant native and exotic woody species? and (2) if this local segregation does exist, is it driven by environmental features?. For this, in 2010 we established 31 plots distributed along 16 sampling sites where we surveyed the composition and abundance of all woody species with a basal diameter ≥ 5cm. To characterize the environment of each plot, we measured the topographic position (slope, exposure) and different properties such as soil physics (bulk density, soil impedance), structure (soil deep, texture) and chemical characteristics (pH, nutrient and water content). Through a cluster analysis we were able to identify five different woody communities in coexistence: (1) Woodlands dominated by the exotic Ligustrum lucidum; (2) Mixed woodlands dominated by the native Lithraea molleoides and the exotic Celtis australis; (3) Scrublands dominated by the native Condalia buxifolia; (4) Scrublands dominated by the exotic Cotoneaster glaucophyllus, and (5) Scrubby grasslands with the exotic Pyracantha angustifolia. These communities were all associated with different local topographic and edaphic features. The environmental segregation among the identified communities suggests that woody invaders have the potential to colonize almost all the environments of the study site (though varying in the identity of the dominant exotic species). The observed patterns, even being restricted to a single well invaded area of mountain Chaco, may posit the spread of woody invaders towards native communities in the region.